1980
DOI: 10.1210/jcem-51-3-599
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-Induced Differential Regulation of β-Adrenergic Receptors in Circulating Human Polymorphonuclear Leukocytes and Mononuclear Leukocytes*

Abstract: A method of reproducibility measuring human leukocyte beta-adrenergic receptor density and affinity has been developed and applied to the study of receptor regulation in man. The method has the advantages of using a membrane preparation which binds highly specifically and employing techniques such as using low concentrations of [3H]dihydroalprenol, analyzing the data by computer modelling techniques, and providing data from both granulocytes and lymphocytes in the same individual to minimize measurement errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(48 citation statements)
references
References 15 publications
4
44
0
Order By: Relevance
“…Other contributing factors might be the different ionic concentrations of the incubation media used for both systems and the possible changes in membrane structure induced by the cell disruption procedure. It should be noticed that other investigators using different homogenization procedures found K D values comparable with those of the intact cell system (Davies and Lefkowitz, 1980;Ginsberg et al, 1981).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Other contributing factors might be the different ionic concentrations of the incubation media used for both systems and the possible changes in membrane structure induced by the cell disruption procedure. It should be noticed that other investigators using different homogenization procedures found K D values comparable with those of the intact cell system (Davies and Lefkowitz, 1980;Ginsberg et al, 1981).…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, considerable differences have been reported in the characteristics of specific [3H]DHA binding to human lymphocyte membrane preparations (e.g. Williams et al, 1976;Sheppard et al, 1977;Brooks et al, 1979;Bishopric et al, 1980;Davies and Lefkowitz, 1980;Tohmeh and Cryer, 1980). Although differences in cell disruption procedures may have contributed to this variability (Davies and Lefkowitz, 1980), another important factor may be the different ways which have been used to define non-specific binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that ␤1AR expression in adult animals and humans is influenced by thyroid hormones (27)(28)(29)(30)(31)(32). Studies from our group and others have shown that the ␤1AR is expressed during late fetal development in both rodents and sheep and coupled to important physiologic responses (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Otherwise glucocorticoid hormones have been shown to have physiological actions on multiple cellular processes; thus, the indirect, so-called 'permissive' actions may involve the modulation of the affinity and/or receptor concentrations of a variety ot ~ heterologous hormone and growth factor receptors [28][29][30][31][32][33][34][35][36][37][38][39][40]. So, given the data presented in this paper, ACTH could regulate its own receptor in adipocytes early during adipose tissue formation via glucocorticoid secretion from the adrenal gland; thus a dual effector mechanism of ACTH action should be retained to render an account of the biological response of the adipose cell to this hormone.…”
Section: Discussionmentioning
confidence: 99%